The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/mcb.23.12.4121-4125.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Damage Type on Stimulation of Human Excision Nuclease by SWI/SNF Chromatin Remodeling Factor

Abstract: To investigate the repair of different types of DNA lesions in chromatin, we prepared mononucleosomes containing an acetylaminofluorene-guanine adduct (AAF-G), a (6-4) photoproduct, or a cyclobutane pyrimidine dimer (CPD) and measured the repair of these lesions by reconstituted 6-factor human excision nuclease. We find that incorporation into nucleosomes inhibits the repair of CPD more severely than repair of the AAF-G adduct and the (6-4) photoproduct. Equally important, we find that SWI/SNF stimulates the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 41 publications
6
45
0
Order By: Relevance
“…This is expected since in vitro studies have suggested that SWI/SNF has an important role in chromatin remodeling and efficient NER of UV lesions (13,14). Studies in yeast as well as in mammalian cells also indicated that SWI/SNF is indispensable for NER (15,16).…”
Section: Brg1 Modulation Against Different Types Of Uv Lesions-wementioning
confidence: 90%
See 2 more Smart Citations
“…This is expected since in vitro studies have suggested that SWI/SNF has an important role in chromatin remodeling and efficient NER of UV lesions (13,14). Studies in yeast as well as in mammalian cells also indicated that SWI/SNF is indispensable for NER (15,16).…”
Section: Brg1 Modulation Against Different Types Of Uv Lesions-wementioning
confidence: 90%
“…Although SWI/SNF has been implicated in regulating the chromatin remodeling process in NER by a number of in vitro excision assays (13,14), its exact role in NER has not been investigated in mammalian cells. In this report, we provide the first time evidence that Brg1 directly interacts with NER factor XPC, affecting NER protein stability (XPC) and/or factor recruitment (XPG and PCNA) leading to efficient repair in human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide excision repair is another example for which the presence of nucleosomes is also inhibitory (16)(17)(18)(19)(20). Furthermore, chromatin remodeling factors, which serve to recover nucleotide excision repair on synthetic dinucleosomes, have been shown to be inhibited by the presence of histone H1 within the nucleosomal arrays (21,22,43). Interestingly, this inhibition can be overcome by linker histone phosphorylation with a known linker histone kinase, Xenopus Cdc2͞Cyclin B.…”
Section: Discussionmentioning
confidence: 99%
“…Now that many repair processes can be reconstituted in vitro, studies are beginning to examine the impact of chromatin structure on repair. Nucleotide excision repair and base excision repair were shown to be impaired on nucleosome substrates relative to naked DNA (16)(17)(18)(19)(20) and repair efficiencies are recovered by the presence of ATP-dependent chromatin remodeling factors (21)(22)(23). In contrast, human DNA ligase I and Flap I endonuclease function efficiently on model nucleosome substrates (24,25).…”
mentioning
confidence: 99%